Increasing Flora And Fauna Biodiversity In The Hengjaya Mineralindo Bio-Spark Program (Jurnal Pengelolaan Lingkungan Pertambangan, 2025)
Indonesia as a country  geographically located between the Asian Continent and the Australian Continent, commonly called the Wallace region, consequently  Indonesia have an abundance of flora and fauna. Over time, the diversity of flora and fauna that exist can be threatened by increased human activities such as mining, and others. PT Hengjaya Mineralindo, a nickel mining company in the Sulawesi region, is aware of the importance of maintaining the biodiversity of flora and fauna around its operational area. The company committed to establishing a High Conservation Value Area of 196.78 ha called BIO-SPARK (Biodiversity Study and Protection for Advancing Research and Knowledge). Based on its diversity index, mammals in the arboretum area have a value of 1.28, which is included in the moderate category, While the avifauna in the arboretum area has a value of 3.35, this value is included in the high category. Based on the evenness index of mammal and avifauna species, the value is close to 1, which means that the distribution of individuals between species is relatively even, and the dominance index is close to 0, which means that there is no dominant species at the monitoring area. The migration of several species from their previous location to the arboretum area, along with the abundance of food supplies available, can lead to the addition of new species. Thus, with the arboretum area, it can be a place to maintain the sustainability of flora and fauna around the PT Hengjaya Mineralindo mining area